Penggunaan Aplikasi Duolingo Dalam Meningkatkan Literasi Berbantuan Aplikasi Capcut - Samuel Juliardi Sinaga; Sartika Evitauli Sianturi; Jelita Pakpahan; Ayen Sitohang; Risna Veronika (CV Putra Publisher, 2024)
This program aims to see the use of the Duolingo application in increasing literacy with the help of the Capcut application. The implementation of PkM at SMA 37 PGRI BATANGKUIS uses a digital literacy approach method through the Duolinggo application assisted by the CapCut application. Where the implementation of PkM aims to overcome the problem of insufficient literacy in order to increase students' literacy in understanding foreign language vocabulary (English). The implementation method that we have developed involves active collaboration between the PkM team and the school, especially the students of SMA 37 PGRI Batangkuis. From the results of this PkM implementation, it can be concluded that the community service program which utilizes the Duolingo and CapCut applications for SMA 37 PGRI BATANGKUIS students has had a positive impact, including: Community service program which utilizes the Duolingo and CapCut applications for students of SMA 37 PGRI BATANGKUIS managed to increase their literacy significantly. Pre-test and post-test data show consistent improvements in students' reading, writing and speaking skills after participating in this program. The integration of the Duolingo application effectively enriches students' foreign language skills, while the use of CapCut provides an additional dimension in the development of students' multimedia skills.